Surface effects on thermoelectric properties of metallic and semiconducting nanowires. Issue 3 (14th October 2015) - Kojda, Danny; Mitdank, Rüdiger; Weidemann, Stefan; Mogilatenko, Anna; Wang, Zhi; Ruhhammer, Johannes; Kroener, Michael; Töllner, William; Woias, Peter; Nielsch, Kornelius; Fischer, Saskia F.
Abstract : Metallic and semiconducting nanowires (NWs) are of interest in the field of thermoelectrics, because they act as model system to investigate the influence of surfaces on the thermoelectric transport properties. In single crystalline NWs, the grain boundary scattering is negligible and the surface‐to‐volume‐ratio is high. We present state‐of‐the‐art of the combination of the structural, chemical, and temperature‐dependent full thermoelectric characterization for individual single crystalline NWs, which is essential to conclude on surface effects. Temperature‐dependent measurements allow further conclusions on the scattering mechanisms. Simulations by the finite element method are performed on indented NWs to interpret the measurement results. Calculated surface temperature of a single‐indented and a multi‐indented NW. Abstract : Combined thermoelectrical, structural and chemical characterisation of individual metallic and semiconducting nanowires is presented. In the temperature range between 4.2 K and room temperature the thermoelectrical properties are determined. Transmission electron microscopy yields the structural properties, the chemical composition and the morphology of the nanowires. This comprehensive study unambiguously allows identifying surface effects on the thermoelectric properties and scattering mechanisms for electrons and phonons.